Efficacy and safety of total dose infusion of low molecular weight iron dextran in the treatment of iron deficiency anemia during pregnancy - Ayub, Rukhsana; Tariq, Nabia; Adil, Malik Muhammad; Iqbal, Mobeen; Junaid, Ayesha; Jaferry, Tara (Journal of the College of Physicians and Surgeons--Pakistan, 2008)
To determine the efficacy and safety of Total Dose Infusion (TDI) of low molecular weight iron dextran for the treatment of iron deficiency anemia compared to oral iron replacement during pregnancy through improvement in hemoglobin (Hb) after intervention. Non-randomized control trial. Section of Gynaecology and Obstetrics, Shifa International Hospital and Shifa Community Health Centre, Islamabad during January 2005 to January 2006. A group of 100 pregnant women with gestational age greater than 12 weeks with confirmed diagnosis of iron deficiency anemia attending the antenatal clinics were enrolled in this study. Total dose iron infusion of low molecular iron dextran was given to these patients after calculating iron deficit, in a monitored in-patient setting. Control comprised of a second group of 50 pregnant females matched for age, parity and baseline hemoglobin, tolerant to oral iron supplementation (ferrous sulphate 200 mg three times a day) attending the antenatal clinics during the same period. Post-treatment hemoglobin levels of study group as well as the oral control group were determined between 3 to 4 weeks. In the intervention group, mean pre-infusion hemoglobin level was 8.57 +/- 0.9 gm/dl (range 5-10.5 gm/dl) and mean post-infusion Hb was 11.0 +/- 1.1 (range 8.4-14.3 gm/dl). In control group, mean pre-oral intake Hb level was 9.5 +/- 0.9 gm/dl (range 7-10.5 gm/dl) and mean post-oral intake Hb was 10.2 +/- 1.2 gm/dl (range 6.4-12.8 gm/dl). Mean increase of Hb in intervention group was 2.43 gm/dl (95% CI 2.4 - 3.8) and for controls it was 0.7 gm/dl (95% CI 0.6-2.3). Flushing and palpitations were observed in 4% of interventional group patients and none in the control group. No significant adverse reactions were observed in either group. We conclude that the total parenteral iron replacement with low molecular weight iron dextran is an effective and safe method for the treatment of iron deficiency anemia in a selected group of pregnant women.